A Novel Screening Tool for Assessing Child Abuse: The Medical Somatic Dissociation Questionnaire–MSDQ. Issue 5 (4th July 2019) - Daphna-Tekoah, Shir; Lev-Wiesel, Rachel; Israeli, David; Balla, Uri
ABSTRACT: Somatic dissociation is known to be associated with childhood abuse, particularly with childhood sexual abuse (CSA). Currently, the diagnosis of CSA is hampered by the lack of a validated questionnaire. While some questionnaires are excellent research tools, there is no suitable applied measure for the assessment of distress due to CSA. The current study's objective was to validate a novel questionnaire, designated the Medical Somatic Dissociation Questionnaire–MSDQ, for evaluating somatic dissociation in the healthcare system setting. A total of 541 adults, 160 (30%) male and 381 (70%) female, of average age 35 years were recruited from the general population via the Internet. The Life Events Checklist for DSM-5 (LEC-5) was used for screening subjects for reporting a history of CSA. Our examination of the MSDQ indicated powerful internal consistency, reliability, and convergent validity of the instrument, with high correlations between the MSDQ and the SDQ-20 and also between the MSDQ and psychological symptomatology. In addition, there was known-groups validity when differences between adults who experienced CSA and those who did not were compared. Importantly, the MSDQ can be easily integrated into the evaluation process performed by medical professionals in the diagnosis of adult patients with apparently unexplained symptomatology.